Flies specimens collected from Agricultural Park, Teluk Cempedak and Bukit Pelindung in Kuantan, Pahang - Heo, Chong Chin; Mohamad Abdullah Marwi,; John Jeffery,; Ismarulyusda Ishak,; Baharudin Omar, (Penerbit UKM, 2008)
This study was carried out in Agricultural Park, Teluk Cempedak and Bukit Pelindung at Kuantan, Pahang in October 2007. These three areas were different in ecological characteristic, Agricultural Park is a lowland region in Kuantan rural area, Teluk Cempedak is Kuantan’s most famous beach, and Bukit Pelindung is a reserved rainforest which is 200 meters from the sea level. Fly specimens were collected using four different kinds of baits: dry prawn, salted fish, pork and mango. Each of these baits was placed in a plastic container and exposed for one hour to attract flies. Within 5 minutes, flies started swarming around the baits. The flies were more attracted to the pork and salted fish compared to the other two baits. Fifty one flies, one moth (Lepidoptera) and one wasp (Hymenoptera) were collected. In Agricultural Park, two Lucilia cuprina, one Chrysomya megacephala and one Sarcophaga sp. were collected. For Teluk Cempedak beach, there were two Sarcophagids, 31 Chrysomya megacephala, five Musca domestica, one Lucilia cuprina and one moth were caught. Flies collected from Bukit Pelindung included five C.megacephala, two Sarcophagids, one Musca domestica and one wasp. Most C.megacephala were attracted to the pork and salted fish.